A Pneumonia That Will Not Go Away - Khaled R Khasawneh; Tashfeen Mahmood; Ruba A Halloush; Faisal A Khasawneh (Canadian Respiratory Journal)
Pneumonia is a common diagnosis with significant morbidity and mortality. However, pneumonia is a commonly overdiagnosed entity, with many similar-appearing conditions. A young, previously healthy woman was misdiagnosed with a variety of respiratory tract infections over the course of five months before establishing the correct diagnosis – chronic eosinophilic pneumonia.